Bisphenol A Exposure and Health Risks - Erkekoglu, Pinar; Kocer-Gumusel, Belma (IntechOpen, 2017)
Bisphenol A (BPA) is a synthetic compound for hardening and clearing polycarbonate plastics. BPA is mainly classified as an estrogen-like endocrine-disrupting chemical. In the last decade, attention has arisen in scientific communities that it is not safe to use this chemical in mainly polycarbonate plastics. Exposure to BPA starts in prenatal period, which is the critical period for its toxic effects on different organs. Throughout this book, the readers will obtain information on the effects of BPA on different systems. They will also get information on the prenatal and postnatal effects of BPA. We believe that readers will get qualified scientific knowledge and a general overview of the toxic effects of BPA exposure and its consequences from this book.